The effect of prednisolone on sperm viability, sperm penetration rate and intra-uterine insemination rates in men with marked sperm agglutination and antisperm antibodies - R., Al-Barazanchi M.T.; M., Alansari S.A.; D., El-Yassin H.; M., Taiyeb A.; S., AL-Atraqchi; A., Kanan Z. (Journal of the Faculty of Medicine Baghdad, 2005)
Summary: Background: the immune system differentiates between the endogenous and exogenous bodies that inter the body. The break-down of blood-testis barrier results in the production of antisperm antibodies. This may occur in the case of an infection to the prostate, seminal vesicle and epididymes. Antisperm antibodies (ASA) cause sperm agglutination and affect sperm motility, viability and sperm migration in the female reproductive tract. ASA also impair fertilization process. The objective of the present work was to study the effect of prednisolone on sperm motility index (SMI), viability and sperm penetration assay (SPA) in immunologically infertile men. Materials and methods: The semen and serum samples of 140 infertile men were examined by microagglutination test and slide agglutination test to detect ASA and sperm agglutination. Semen fliud analysis was performed to report sperm motility index (SMI), sperm viability and hypo-osmotic swelling test (HOST). Sperm penetration assay was done to record sperm penetration rate (SPR), sperm decondensation rate (SDR) and sperm penetration index (SPI). Men with positive ASA were treated with prednisolone and considered as treated group Prednisolone was given orally in a dose of 5 mg three times daily for three months. The semen analysis, SMI HOST and SPA were performed before and after treatment with prednisolone. The number of semen samples in the treated group was 144 and in the control fertile group was 80. HOST-SPA positive semen was exposed to antisperm antibodies separation (ASAS) and invitro sperm activation prior to intra-uterine insemination. Results: The SMI was significantly higher in the post-treated group compared to pretreated group (240 vs. 52.5, P<0.0l). The SPI in the control group was significantly higher than the post and pre-treated groups. The HOST and viability test results were significantly increased in the post-treated group compared to pre-treated group (73.42 vs. 48.56 and 71.36 vs, 50. 74 respectively, P<0.01). The sperm penetration rate, sperm decondensation rate and sperm penetration index were significantly increased in the post-treated vs. pre-treated groups (26.49 vs. 10.84, 10.91 vs. 3.47, P<0.05, 14.45 vs. 4.30, P<0.01 respectively). HOST-SPA positive semen was used for intra-uterine insemination (IUI). The semen was exposed to ASAS and in vitro activation prior to IUI and resulted in 42.86% pregnancy rate per cycle. The pregnancy was confirmed by the observation of gestation sac and viable fetal hear beet 5 weeks following IUI. Conclusion: It was concluded from the results of the present study that treatment of immunological infertile men with prednisolone improves SMI, sperm viability and SPA results. The application of HOST-SPA positive semen for IUI resulted in successful pregnancy. The authors indicate that these viable spermatozoa with high fertilizable potential could be used for IVF and/or ICSI in immunologically infertile men.